2011
DOI: 10.1017/s000711451100554x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal undernutrition during critical windows of development results in differential and sex-specific effects on postnatal adiposity and related metabolic profiles in adult rat offspring

Abstract: It is well established that altered maternal nutrition may induce long-term metabolic consequences in offspring. However, the effects of maternal undernutrition during different developmental windows on sex-specific growth and metabolism in offspring are not well defined. We investigated the effect of moderate maternal undernutrition during pregnancy and/or lactation on postnatal growth and metabolic outcomes in offspring. Wistar rats were randomly assigned to one of four groups: (1) control (CONT) dams fed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 41 publications
6
53
2
1
Order By: Relevance
“…This has been previously demonstrated in adult offspring from similar IUGR models [23,24] and can be prevented by dietary interventions which avoid catch-up growth during suckling period [24]. These data indicate that perinatal life is a critical developmental window during which the alterations induced by IUGR might further develop.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This has been previously demonstrated in adult offspring from similar IUGR models [23,24] and can be prevented by dietary interventions which avoid catch-up growth during suckling period [24]. These data indicate that perinatal life is a critical developmental window during which the alterations induced by IUGR might further develop.…”
Section: Discussionsupporting
confidence: 69%
“…To assess our hypothesis we have studied a rat model of IUGR induced by maternal undernutrition during the second half of gestation (MUN), which has been previously demonstrated to program for hypertension and obesity in adult age [5,[21][22][23][24]. In male and female offspring from MUN and Control dams, we have assessed individual plasma biomarkers of oxidative damage and antioxidant capacity and calculated a global score (oxy-score) from them.…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that protein restriction during the beginning of adulthood changes glucose and energy metabolism, which might persist in the later stage of life even when the LP diet intervention had been removed. Protein malnourishment during pregnancy causes evident obesity when the rodents reach adulthood (Anguita et al 1993, Fernandez-Twinn & Ozanne 2006, Howie et al 2012; however, the current study does not provide strong enough evidence to indicate that a LP diet during young adulthood provokes obesity later in life. The current results indicate the induction of a slight increase in fat tissue, which is supported by a modest increase in insulin blood levels after a glucose bolus infusion.…”
Section: Discussioncontrasting
confidence: 57%
“…Despite no differences in birth weight between experimental groups, HF-HF offspring started to become heavier 3 wk following weaning. Thus, unlike in some models of intrauterine undernutrition such as maternal protein restriction (3,11,17,31) or caloric restriction (3,11,31), which are often characterized by lower offspring birth weight, offspring born to high-fat/fructose fed mothers, as observed in the present study, seem to exhibit a delayed response with respect to changes in body weight. Similar observations were made in other rodent models of maternal overnutrition (4,10,20,22,27).…”
Section: Discussioncontrasting
confidence: 75%
“…As mentioned earlier, models of intrauterine undernutrition as a result of maternal protein restriction (3,11,17,31) as well as models of maternal overnutrition (4,10,20,22,27) are associated with a cardiometabolic phenotype in the offspring. Our own study, which utilized high-fat/fructose feeding also showed a similar phenotype in the offspring.…”
Section: Discussionmentioning
confidence: 85%